Chinook salmon rearing habitat–discharge relationships change as a result of morphodynamic processes. (6th September 2021) - Moniz, Peter J.; Pasternack, Gregory B.
Abstract: Relationships between fluvial aquatic habitat availability and discharge are often assumed to remain static when used with hydrologic datasets to analyze changes in habitat availability over time. Despite this assumption, studies have observed significant changes in aquatic habitat availability before and after restoration projects, dam removals, and extreme flood events. However, research is lacking on how aquatic habitat changes as a result of morphodynamic processes during more commonly occurring hydrologic conditions. This study compared Chinook salmon ( Oncorhynchus tshawytscha ) rearing habitat availability at 19 discharges before and after a relatively mild 8‐year hydrologic period punctuated with modest floods on the lower Yuba River in California, USA. During this time, the total area of rearing habitat remained relatively consistent at discharges <2× bankfull but decreased by up to 25% at discharges >2× bankfull. Significant decreases in rearing habitat area appeared to be the result of widespread erosion on floodplains, terraces, and lateral bars, even after only modest floods. As a result, spatially delineated areas of lost habitat tended to increase in water depth and velocity at baseflow, bankfull, and floodplain‐filling discharges, while areas of gained habitat decreased in depth and velocity. Although these specific results may not apply to all rivers around the world, the finding that habitat–discharge relationships change as a result of morphodynamic processes likely does transfer globally and should be considered when making long‐term regulatory and management decisions, such as instream flow requirements and habitat restoration plans.